"Adieu ihr lieben Schwarzen" Gesammelte Schriften des Tiroler Afrika-Missionars Franz Mayr (1865-1914) - Gütl, Clemens (2004)
Franz Mayr was "one of the most interesting of catholic missionaries in Southern Africa" states Professor Joy Brain ("University of Durban") in the foreword she wrote for this first edition of his writings. Mayr was born in the Austrian province of Tyrol in 1865, educated as a priest in the diocese of Brixen and arrived in Natal (South Africa) at the beginning of May 1890, inspired by the work being done there by the Trappist-Monks led by Abbot Franz Pfanner. Mayr was physically handicapped and soon left the trappists but just to offer his services to the vicar apostolic of Natal, Bishop Charles Jolivet, who accepted him for work among the African population. He was sent to Pietermaritzburg then capital of the British colony to take over the care of the African parishioners to bring the "good news" to those who had never heard it. He founded several new mission-stations in Natal, Southern Rhodesia (present day Zimbabwe) and Swaziland where he was killed by a native robber in 1914. Mayr - a man of many talents - was a gifted linguist, studied and published books in several African languages. He was interested in cultural anthropology and collected information about African customs. It is now more than a hundred years since Franz Mayr began his work of evangelisation and scholarship in Southern Africa. Publishing his letters and articles - kept by several archives in Europe - should help to remember a man of the Habsburg-Monarchy who went to preach the gospel to the so called heathen of Africa. Although Austria or Austria-Hungary never owned colonies in Africa many of its inhabitants left their homes to work in catholic mission-stations around the continent. Several introductory chapters in this book explain the particular historical context which has to be put into consideration when reading Mayrs' writings. From there we learn about his life, his work, how he treated the native population, what he thought about other religious congregations around him, the colonialists and about troubles when trying to convince people to believe in the only - the "European God". The missionary deserves to be better known. The present edition of historical sources is to be seen as a most relevant step allowing us to interpret his personality adequately.